CORRELATION BETWEEN BODY MASS INDEX (BMI) AND FEMOROTIBIAL JOINT SPACE WIDTH ON LYON-SCHUSS KNEE RADIOGRAPHS IN PATIENTS WITH KNEE OSTEOARTHRITIS AT H. ADAM MALIK GENERAL HOSPITAL, MEDAN, IN 2025 - Asrini Rizky Nasution; Henny Maisara Sipahutar; Husnul Fuad Albar (PT. Radja Intercontinental Publishing, 2025)
Background: Knee osteoarthritis (OA) is the most common form of osteoarthritis and a frequent cause of chronic health problems. The femorotibial joint space is one of the most predictive factors associated with clinical symptoms and outcomes in patients with knee OA. Obesity is a major risk factor for the development of knee OA. Measurement of the knee joint space is most accurately performed using the Lyon-Schuss position. Methods: This study is an analytic study with a cross-sectional design. Radiological examinations were performed in the Lyon-Schuss position, and the narrowest femorotibial joint space was measured. Bivariate analysis using the chi-square test The Mann-Whitney U and Kruskal-Wallis test. Correlation analysis was then performed to determine the strength of the relationship between BMI and femorotibial joint space width. Results: Bivariate analysis showed a relationship between BMI and OA grade (p = 0.093), as well as between femorotibial joint space width and both BMI (p = 0.000) and OA grade (p = 0.000). A negative correlation was found between BMI and femorotibial joint space width, with the regression equation: y = 8.577 - 0.255x, where y represents femorotibial joint space width (mm) and x represents BMI (p = 0.000; R² = 0.306). Conclusion: There is a negative correlation between body mass index and femorotibial joint space width in patients with knee osteoarthritis.